Uses for expanded production of natural gas liquids: chemicals or power?. Issue 1 (14th September 2017) - Allen, David T.; Cardoso‐Saldaña, Felipe J.; McGaughey, Gary; McDonald‐Buller, Elena; Webster, Mort
Abstract : Expanded production of natural gas liquids (NGLs, ethane, propane, butanes) in the United States may continue to be utilized in domestic and international chemical manufacturing; however, this would require the development of expanded transport infrastructures. Electricity generation is an alternative use for NGLs. As a case study of the value of NGLs in electricity generation, the potential use of NGLs in the Texas electrical grid was evaluated. It was assumed that electricity would be generated in 25‐MW gas turbines, located at gas‐processing plants where NGLs in produced gas are separated to create pipeline‐quality gas. The potential magnitude of NGL‐based power generation in the Texas grid, using NGLs produced in the Eagle Ford and Barnett oil and gas production regions in Texas, was estimated to be up to 2.7 GW of electricity, 6% of average demand on the grid. The NGL‐based electricity generation displaced coal and natural gas‐based generation, with little impact on the use of renewables. At the assumed efficiency (34.7%) and nonfuel operating cost (7/MWh) of small gas turbines, NGLs are only fully utilized for electricity generation in the Texas grid when fuel prices are lower than 1.50 per million BTU (a discount of 0.90 per million BTU relative to the fuel price of coal assumed in the modeling). Higher prices might be supported if NGLs are used for electricity generation at times of high demand or if larger, higher efficiency turbines are utilized. WIREs Energy Environ 2018, 7:e258. doi: 10.1002/wene.258 This article is categorized under: Fossil Fuels > Systems and Infrastructure Energy Infrastructure > Systems and Infrastructure Abstract : Electricity generation, as an alternative to chemical manufacturing, for the use of natural gas liquids is assessed